Limnodrilus sulphurensis n. sp., from a sulfur cave in Colorado, USA, with notes on the morphologically similar L. profundicola (Clitellata, Naididae, Tubificinae) - Fend, Steven V.; Liu, Yingkui; Steinmann, David; Giere, Olav; Barton, Hazel A.; Luiszer, Fred; Erséus, Christer (Zootaxa, 2016)
A new species of the tubificine genus Limnodrilus is described and COI barcoded from Sulphur Cave and associated springs in Colorado, USA. The habitats are characterized by high sulfide concentrations. The new species, L. sulphurensis, is distinguished from all congeners by the elongate, nearly parallel teeth of chaetae in its anterior segments. It has a penis sheath resembling that of L. profundicola; consequently, museum specimens and new collections are examined here to resolve some of the taxonomic confusion surrounding that widespread, but uncommon species.